(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
An experiment was conducted to evaluate the morphological characterization of five germplasm of Sapota namely BAU Sapota-1, BAU Sapota-2, BAU Sapota-3, Deshi Sapota and Vietnam Sapota. Randomized complete block design with three replications was performed for investigating the morphology of Sapota. Results indicate that the tallest plant was Deshi Sapota and the shortest plant was BAU Sapota-2. Also, the highest stem circumference was found in Deshi Sapota which was 52.25 cm. The maximum spreaded plant both in north-south and east-west direction was found in BAU Sapota-1 which was 1.62 and 1.53 m, respectively. Maximum shoot girth was found in BAU Sapota-3 and BAU Sapota-1 plants showed the most vigorous growth whereas BAU Sapota-3 had the longest shoot length. Results revealed that significant difference (p<0.01) present in leaf length, lamina length and petiole length among the variety of Sapota. Higher numbers of flower per shoot was found in BAU Sapota-3 whereas the highest fruit setting time was observed in Deshi Sapota. The BAU Sapota-3 produced the heaviest fruit while the lightest fruit was recorded in BAU Sapota-2. The longest fruit length, highest moisture content and maximum total soluble solids were found in BAU Sapota-3. Correlation coefficient study indicated that plant height, leaf length and fruit length had positive and highly significant association with stem circumference, leaf lamina length, % moisture and fruit yield, respectively. In respect of path analysis, plant height, tree growth, leaf length, fruit setting time, fruit fresh weight, % moisture content and total soluble solids positively affected on fruits per plant indicating its importance as a selection parameter. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 108-115